2018
DOI: 10.1039/c8nj03417f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular iodine-catalysed oxidative CO–C(alkyl) bond cleavage of aryl/heteroaryl alkyl ketones: an efficient strategy to access fused polyheterocycles

Abstract: An efficient molecular iodine-catalysed one-pot strategy has been accomplished for the construction of various fused heterocycles under metal and oxidant free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Finally the oxidative aromatization of M affords the desired product 3 . It is known that molecular iodine can be regenerated from HI by DMSO ,. [21e] In this reaction, I 2 acts as an iodinating reagent (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally the oxidative aromatization of M affords the desired product 3 . It is known that molecular iodine can be regenerated from HI by DMSO ,. [21e] In this reaction, I 2 acts as an iodinating reagent (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, I 2 /DMSO catalyzed oxidative cross‐coupling reactions have been reported for the synthesis of 2‐benzoyl pyridoimidazole . Later on, iodine‐catalyzed one‐pot sequential C–N and C–C bond forming reactions have been developed to generate N ‐fused heterocycles . However, there are no reports on the synthesis of N ‐fused polyheterocycles through an oxidative sp 3 C–H functionalization of methyl‐substituted aza‐aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…The classical methods are the Bischler–Napieralski type reactions of N -(2-acylaminophenyl)-pyrroles using dehydrating reagents such as POCl 3 (Scheme 1A). 14 The most common methods are Pictet–Spengler type reactions between 2-(1 H -pyrrol-1-yl)anilines and cyclization partners such as aldehydes, 15 alcohols, 16 amines, 17 alkyl halides, 18 ketones, 19 1,3-diketones, 20 α-keto acids, 21 α-hydroxyl acids, 22 α-amino acids, 23 aryl acetic acids, 24 cyclic ethers, 25 and methyl arenes 26 in the presence of various oxidants (Scheme 1B). 27,28 Although these oxidants facilitated Pictet–Spengler type pyrrolo[1,2-α]quinoxaline synthesis, a high reaction temperature was usually required and the substrate scope was mostly limited to 4-aryl substituted pyrrolo[1,2-α]quinoxalines.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In the past few decades, direct CÀ H functionalization has been favored by many researchers due to the low-cost starting materials, the highly selective step, and atom economy. [15] The CÀ H activation of quinoxaline at the C3 position has been widely reported including the reaction of quinoxalinone with arylboronic acids, amidates, aliphatic amines and ammonium thiocyanate. [16] However, only a few studies have been reported on the benzylation of quinoxalinone at C3.…”
Section: Introductionmentioning
confidence: 99%